Central AdS Generalized Ayón-Beato-García Black Holes and Joule-Thomson Expansion - Elham Ghasemi; Hossein Ghaffarnejad (Iranian Journal of Astronomy and Astrophysics)
In this paper, the Joule-Thomson (JT) adiabatic expansion isinvestigated for generalized Ayon-Beato-Garcia (ABG)\textcolor[rgb]{0.00,0.00,1.00}{regular} black hole. It has amagnetic charge which makes central region of the black holemetric to be AdS spacetime and so become non singular.\textcolor[rgb]{0.00,0.00,1.00}{Thus we not need to use anadditional cosmological parameter coming from ADS/CFTcorrespondence for production of pressure coordinate in the blackhole equation of state. Form this point of view our work is a newapproach versus to conventional methods which are addressed in thereferences of this paper. However we will see important behaviorof parameters of this modified ABG black hole on possibility ofbeing of JT adiabatic expansion.} This black hole is characterizedby five parameters including mass $m$, magnetic charge $q$, andthree \textcolor[rgb]{0.00,0.00,1.00}{other} parameters related toform of used nonlinear electromagnetic interaction fields.\textcolor[rgb]{0.00,0.00,1.00}{Inversion points are in fact aparticular T-P curve at constant enthalpy and it separates coolingand heating phase of the modified AdS ABG black hole.}